Culture Shock in Students from International Academic Mobility (2022)
This study describes the experience of international students while studying overseas, and how interacting with a new culture can cause shock at different levels. For doing so, this research was conducted under qualitative methods and implemented at a public university in Pereira, Colombia. The participants were pupils from inbound and outbound academic mobility that participated in exchange programs offered by the UTP. Every student represented a single case; therefore, this project was a descriptive multicase study. Bearing this in mind, the information was gathered through documents, semi-structured interviews, and questionnaires. To analyze the collected information, the researchers followed a process of contrast and comparison to develop a grounded theory and described the phenomenon under study. Furthermore, based on the findings, it was evidenced that all of the participants went through the four stages of culture shock established by Oberg (1960), and that engaging in these events influenced their lives in the short term; likewise, taking into account the outcomes of this inquiry, the researchers made some suggestions to the ORI, so they can help future international students in their adaptation process. According to Furnham (2010) to diminish the effects of culture shock, it is pivotal that pupils develop Intercultural Communication Competencies (ICC), along with enough accompaniment and orientation during the adjustment to the new cultural and academic systems.